PENGARUH PENGALAMAN AUDITOR DAN AUDIT CAPACITY STRESS PADA KUALITAS AUDIT DENGAN KOMPETENSI SEBAGAI VARIABEL MEDIASI - Sari, Ghema Purnama; Rasmini, Ni Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.04.TAHUN.2023DO - 10.24843/EEB.2023.v12.i04.p02, 2023)
Audit quality is the final result of the audit process in accordance with the audit and reporting standards as well as quality control that has been established, the implementation of auditing practices that can be accounted for by the auditor as a form of professional ethics. This research was conducted at the Public Accounting Firm in Bali Province. The method of determining the research sample is based on the non-probability sampling method with purposive sampling technique. The criteria for selecting the sample are auditors who work in a Public Accounting Firm for at least 1 year, so that 52 auditors are obtained as research respondents. Data were collected through the distribution of questionnaires. The data analysis technique used is path analysis technique. The results of this study conclude that partially the experience of auditor’s audit capacity stress, and competence affect the quality of audits carried out by auditors working at Public Accounting Firms in Bali Province. The results of the study also prove that competence is able to mediate the effect of auditor experience and audit capacity stress on the quality of audits carried out by auditors working at Public Accounting Firms in Bali Province